Early changes of brain perfusion after subarachnoid hemorrhage - the effect of sodium nitroprusside - Kolář, Michal; Nohejlová, Kateryna; Mareš, Jan; Pachl, Jan (Physiological research, 2016)
Causes of early hypoperfusion after subarachnoid hemorrhage (SAH) include intracranial hypertension as well as vasoconstriction. The aim of the study was to assess the effect of intracerebroventricular (ICV) administration of sodium nitroprusside (SNP) on early hypoperfusion after SAH. Male Wistar rats (220-240 g) were used, SAH group received 250 microl of fresh autologous arterial blood into the prechiasmatic cistern; sham-operated animals received 250 microl of isotonic solution. Therapeutic intervention: ICV administration of 10 microg SNP; 5 microl 5 % glucose (SNP vehicle) and untreated control. Brain perfusion and invasive blood pressure were monitored for 30 min during and after induction of SAH. Despite SNP caused increase of perfusion in sham-operated animals, no response was observed in half of SAH animals. The other half developed hypotension accompanied by brain hypoperfusion. There was no difference between brain perfusion in SNP-treated, glucose-treated and untreated SAH animals during the monitored period. We did not observe expected beneficial effect of ICV administration of SNP after SAH. Moreover, half of the SNP-treated animals developed serious hypotension which led to brain hypoperfusion. This is the important finding showing that this is not the option for early management in patient after SAH.
Keywords: Male; zvířata; Cerebrovascular Circulation; intraventrikulární infuze; Nitroprusside; Animals; Rats; Subarachnoid Hemorrhage; Rats, Wistar; nitroprusid; antihypertenziva; Antihypertensive Agents; mozek; Infusions, Intraventricular; potkani Wistar; intrakraniální hypotenze; mozkový krevní oběh; mužské pohlaví; subarachnoidální krvácení; Intracranial Hypotension; Brain; krysa rodu Rattus